Liberalism, democracy, and development - Chan, Sylvia (Cambridge University Press, 2002)
"Many commentators have assumed a close connection between liberal democracy and economic development. Sylvia Chan questions this assumption and suggests a new theoretical framework, in which liberal democracy is 'decomposed' into economic, civil, and political dimensions that can be combined in different ways, allowing for a range of 'institutional matrices'. She then shows, in a case study of Japan and the Asian newly industrialising countries, how these seemingly less democratic countries have enjoyed a unique mix of economic, civil and political liberties which have encouraged economic development without the need to share the institutional structures and cultural values of the West. Chan's model therefore provides a re-evaluation of the institutional capacities needed to sustain a competitive economy in a globalising world, and develops a more sophisticated understanding of the democracy-development connection."--Jacket.